Nigeria : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report assesses accounting and auditing practices within the context of the Nigerian institutional framework to ensure the quality of corporate financial reporting. There is a multiplicity of laws and bodies for the regulation of accounting, financial reporting, and auditing requirements of companies, including differential financial reporting requirements for small companies. However, the accounting and auditing practices in Nigeria suffer from institutional weaknesses in regulation, compliance, and enforcement of standards and rules. Nigerian Accounting Standards (SAS) have not been reviewed or updated in line with current international standards, and in many cases the national and international standards are not equivalent. Compliance with more lenient national accounting standards is achieved, however with some exceptions. National auditing standards do not exist; auditors are advised to follow International Standards on Auditing (ISA) although such compliance is not mandatory, and there appears to be inadequate adherence to auditing standards and professional ethics. Furthermore, ethical codes for auditors in Nigeria are not in line with international requirements. Except within the banking sector, monitoring and enforcement mechanisms are very weak. These factors, as well as poor accounting education and training, have contributed to weaknesses of the financial reporting and auditing regime.